DETERMINAN NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Jaya Kusuma, I Kadek Adi; Sudirman, I Made Surya Negara (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.06.TAHUN.2022, 2022)
Investment is a commitment to place the amount of funds in investment instruments to get unbalanced results in the future. One of the attractive investment instruments is stocks. Firm value is an investor's perception of the company, which is often read by stock prices. The purpose of this study was to determine the effect of profitability, capital structure, and liquidity on firm value in the textile and garment sub-sector listed on the Indonesia Stock Exchange. The population in this study are all textile and garment sub-sector companies listed on the Indonesia Stock Exchange, totaling 21 companies for the 2017-2020 period. The sampling technique used is purposive sampling, so that the final sample obtained is 13 textile and garment sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. Data collection was carried out using non-participant observation methods. The data analysis technique used is descriptive statistics, multiple linear regression analysis, and classical assumption test. The results showed that profitability and capital structure had a positive and significant effect on firm value in textile and garment sub-sector companies. While liquidity has a negative but not significant effect on firm value in textile and garment sub-sector companies. The implication of this research is that the textile and garment sub-sector companies must maintain the company's current profitability so that investors are not afraid to invest, the company must be more conservative in determining the methods and company policies to maintain company value that can be seen based on the company's capital structure, the company should be able to arrange to be able to immediately meet short-term obligations before these obligations mature .